JavaScript unit testing : your comprehensive and practical guide to efficiently performing and automating JavaScript unit testing - Saleh, Hazem (Community experience distilled., 2013)
A practical, example-driven guide to using, automating, and integrating JavaScript Unit tests for the busy and conscientious JavaScript developer striving for excellence and success. JavaScript Unit Testing is a must have guide for every web developer, designer, architect, and JavaScript coder seeking to ensure the highest quality of their web applications and JS code. Knowledge of JavaScript is assumed.